ANALISIS REVENUE SHENANIGANS PADA LAPORAN KEUANGAN PT BUKALAPAK - Meisyah Rambe; Laylan Syafina; Yenni Samri Juliati Nasution (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2024)
Since the disclosure of the financial scandal committed by Enron, which also involved the public accounting firm Arthur Andersen, the topic of financial shenanigans has become a hot topic of discussion in business circles and researchers. After Enron, almost the same scandal also occurred in companies such as Wordcom, Xerox Corporation, and Freddie Mac and Fannie Mae (Agoes, 2019). In Indonesia itself, state-owned companies have also committed manipulation scandals against financial statements. At the end of 2022 PT Bukalapak also reported a profit of Rp1.9 trillion after previously reporting a loss of Rp1.6 trillion. Based on PT Bukalapak's 2022 financial statements, the entity reported a profit of IDR 1.9 trillion or an increase of 218% from 2021. This significant increase in profit is then an interesting red flag for further research.